2017
DOI: 10.1186/s12883-017-0850-1
|View full text |Cite
|
Sign up to set email alerts
|

Bapineuzumab for mild to moderate Alzheimer’s disease: a meta-analysis of randomized controlled trials

Abstract: BackgroundAlzheimer’s disease (AD) is a globally prevalent neurodegenerative condition, clinically characterized by progressive memory loss and gradual impairment of cognitive functions. Bapineuzumab is a fully humanized monoclonal antibody that binds to neurotoxic amyloid proteins in the brain, enhancing their clearance. We performed this systematic review and meta-analysis to evaluate the safety and efficacy of bapineuzumab in patients with mild to moderate Alzheimer’s disease.MethodsWe performed a web-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…, ; Abushouk et al . ), researchers are increasingly pursuing other avenues for future therapeutic targets (Morris et al . ).…”
mentioning
confidence: 99%
“…, ; Abushouk et al . ), researchers are increasingly pursuing other avenues for future therapeutic targets (Morris et al . ).…”
mentioning
confidence: 99%
“…The group sizes in that study were small (N = 38–57 evaluable, depending on the measure) but similar to that which was targeted (N = 75) based on power calculations for a 30% reduction in whole‐brain atrophy. In the bapineuzumab studies, no significant difference in whole‐brain atrophy between treated and placebo groups was observed in any of the four phase 3 trials [8,9] nor in a meta‐analysis of six phase 2 and 3 trials [19]. Moreover, no relationship between brain boundary shift integral and drug exposure levels was observed in an analysis of two of the phase 3 trials [20].…”
Section: Discussionmentioning
confidence: 95%
“…However, in a predefined secondary analysis of subjects with mild (baseline MMSE score 20-26) AD only, pooled across both trials, solanezumab-treated subjects declined more slowly on cognitive and functional measures than placebo-treated subjects [4]. No evidence of slowing of cognitive or functional decline was seen in subjects with moderate (baseline MMSE score [16][17][18][19] disease. Amyloid positron emission tomography imaging, performed in a small subset (N 5 251) of the EXPEDITION and EXPEDITION2 participants with mild AD, revealed that approximately 25% of those subjects were amyloid negative and, in the placebo arm, did not show typical disease progression over the trial duration [5,6].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Alzheimer's disease (AD) is a globally prevalent neurodegenerative condition, clinically characterized by progressive impairment of memory and cognitive functions . At present, there were approximately 36 million AD patients in the world, and it is expected to double every 20 years in future.…”
Section: Introductionmentioning
confidence: 99%